Development of Students Book Based on Metacognition on Immune System Material for Student Class XI SMA/MA - Al Fahrurz; Elsa Yuniarti; Zulyusri Zulyusri; Ganda Hijrah Selaras (Bioeducation Journal, 2019)
The purpose of this research is to develop and show the validity and practically of students book about immune system material based metacognition for student class XI SMA/MA. Type research is research and development. This research applies 3 steps from 4D model, that the are define, design and develop. The subject of the this research are 4 expert as validator, 2 teachers and 25 student classes XI MA Negeri Kab. Lima Puluh Kota. Data gained is categorized into primary data, as it is collected from validity and practically questionnaire which is directly filled by research subjects. The data was analyzed descriptively. The result of validity 3,65 in criteria very valid, practically by teachers is 3,64 criteria very practice and practically by students is 3,42 in criteria very practice. It can be concluded that the students book on immune system material based on metacognition for students class XI SMA/MA is very valid and practically.